Morphology control in microwave synthesized bismuth sulfide by using different bismuth salts. (1st March 2018) - Díaz-Cruz, Evelyn B.; Castelo-González, Omar A.; Martínez-Alonso, Claudia; Montiel-González, Zeuz; Arenas-Arrocena, M.C.; Hu, Hailin
Abstract: Bismuth sulfide (Bi2 S3 ) is a promising semiconductor for optoelectronic applications. In this work we show that different morphologies of Bi2 S3 such as nanofibers, nanorods or nano-hedgehogs, can be obtained by microwave assisted solution synthesis. The morphology of the products largely depends on the bismuth salt sources that manifest different dissociation kinetics. Nanofibers of highly crystalline Bi2 S3 are formed with the slowly dissociated BiCl3, whereas the morphology of "urchin" type is obtained with highly ionic Bi(NO3 )3 . On the other hand, the size of those nanostructures is mostly determined by the thermodynamic parameters of the synthesis, such as the type of solvents, the solution pH, the reaction temperature and the solution concentration. Total diffuse reflectance spectra of the Bi2 S3 products suggest a direct band-gap of 1.3 eV with absorption coefficients as a function of the synthesis process. It demonstrates that the morphology of semiconductor nanostructures of Bi2 S3 can be modified by controlling the reaction kinetics during the nucleation process in microwave synthesis.